"Reservewährungsland wider Willen"? Die Bundesbank, die deutschen Geschäftsbanken und die internationale Rolle der D-Mark (1968-1985); "Reserve currency country against its will"? The Bundesbank, German Commercial Banks and the International Role of the Deutsche Mark (1968-1985) - Matthias Kemmerer (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– During the early post-Bretton Woods era, the Bundesbank discouraged the international use of the Deutsche Mark through collaboration with West German banks. These accommodated the Bundesbank's stability imperative. As a corollary of the mark's enduring international popularity, the home-currency privilege improved the international competitiveness of German banks. Yet with the re-rise of the US dollar in the 1980s, these shared objectives dissipated. The Bundesbank shifted its policy from monetary control towards currency competition, exposing German banks to foreign rivals. The article suggests that domestic monetary stability concerns may outweigh gains in financial liberalisation. This may, however, undermine the ability of domestic banks to adapt to international competition.
Keywords: E58; L51; L43; N24; G18; 330; Deutsche Bundesbank; financial regulation; rent seeking; currency competition; re-serve currency; German banks